Immobilization of nanocatalysts on cordierite honeycomb monoliths for low temperature NOx reduction - Go, Min Jung; Lee, Baeck Kyoung; Kumar, Pullur Anil; Lee, Won Koo; Joo, Oh Shim; Ha, Heon Phil; Bin Lim, Heung; Hur, Nam Hwi (ELSEVIER SCIENCE BV, 2009)
Noble metal nanocatalysts such as Pd, Pt, and Au were strongly immobilized on the inside walls of monolithic honeycomb-structured cordierite, in which bi-functional molecules were used as linkers for anchoring noble metal nanoparticles (NPs) on the cordierite surface. The supported nanocatalysts were characterized by ICP-MS, TEM, and X-ray powder diffraction. The efficiencies of the immobilized nanocatalysts for the removal of harmful nitrogen oxides (NOx) have been investigated by measuring the deNO(x) capability as a function of temperature. The catalytic activities depend mainly on the compositions of the nanocatalysts. The Pd/Pt bi-metal catalyst anchored on the cordierite surface shows higher NOx conversion and better activity than the commercial emission catalyst at low temperature region, which could be due to the large portion of active surface areas of the catalysts with nanometer scale. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SELECTIVE CATALYTIC-REDUCTION; LEAN-BURN CONDITIONS; NITROGEN-OXIDES; HYDROGEN-PEROXIDE; METAL-CATALYSTS; ALUMINA; NANOPARTICLES; HYDROCARBONS; PROPENE; ZEOLITE